Impact of Prior Intra-articular Injections on the Risk of Prosthetic Joint Infection Following Total Joint Arthroplasty: A Systematic Review and Meta-Analysis - Nie, Fei; Li, Wei (Frontiers in Surgery, 2021)
Objective: The current review was designed to assess the impact of prior intra-articular injections on the risk of prosthetic joint infection (PJI) in patients undergoing total joint arthroplasty (TJA) with a focus on the timing of injection before surgery. Methods: The databases of PubMed, Embase and Google Scholar were searched up to 15th June 2021. All studies comparing the incidence of PJI with and without prior intra-articular injections were included. Risk ratios (RR) with 95% confidence intervals were calculated for PJI. Results: Nineteen studies were included. Both corticosteroids and hyaluronic acid injections were used before TJA in the included studies. Overall, comparing 127,163 patients with prior intra-articular injections and 394,104 patients without any injections, we noted a statistically significant increased risk of PJI in the injection group (RR 1.24 95% CI: 1.11, 1.38 I2=48% p=0.002). On subgroup analysis, there was a statistically significant increased risk of PJI in the injection group in studies where intra-articular injections were administered <12 months before surgery (RR 1.18 95% CI: 1.10, 1.27 I2=7% p<0.00001). Furthermore, on meta-analysis, we noted non-significant but increased risk of PJI when injections were administered 1 month (RR 1.47 95% CI: 0.88, 2.46 I2=77% p=0.14), 0-3 months (RR 1.22 95% CI: 0.96, 1.56 I2=84% p=0.11), and 3-6 months (RR 1.16 95% CI: 0.99, 1.35 I2=49% p=0.06) before surgery. Conclusion: Our results indicate that patients with prior intra-articular injections have a small but statistically significant increased risk of PJI after TJA. Considering that PJI is a catastrophic complication with huge financial burden, morbidity and mortality; the clinical significance of this small risk cannot be dismissed. The question of the timing of injections and the risk of PJI still remains and can have a significant impact on the decision making.